U.S. EPA oversight of pesticide traits in genetically modified plants and recent biotechnology innovation efforts - Mendelsohn, Michael; Pierce, Amanda A.; Striegel, Wiebke (Frontiers in Plant Science, 2023)
Before pesticides can be sold in the United States, the United States Environmental Protection Agency (EPA) must evaluate them thoroughly to ensure that they meet U.S. federal pesticide registration standards for human health and the environment. EPA considers pesticidal substances produced and used in plants as pesticides and defined them in the regulations as “plant-incorporated protectants” (PIPs). PIPs that are created through conventional breeding are exempted from registration requirements, while those created through biotechnology require individual assessments and approval by EPA before they can be distributed or used. This currently includes PIPs that are identical to those that could be moved through conventional breeding but are created through biotechnology (e.g., through genome editing or via precision breeding techniques). EPA proposed an exemption in October 2020 to allow certain PIPs created through biotechnology to be exempt from EPA requirements for pesticides where those PIPs: 1) pose no greater risk than PIPs that EPA has already exempted, and 2) could have otherwise been created through conventional breeding.